PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMP N 15 PADANG - Amelia, Sinta (Jurnal Edukasi dan Penelitian Matematika, 2023)
Problem solving ability is one of the objectives of learning mathematics that must be achieved by students. However, in reality students' mathematical problem solving abilities in schools are still low. One effort to overcome this problems is to apply the Problem Based Learning model. The ultimate goal of this research is to find out whether the mathematical problem-solving abilities of students who study with the Problem Based Learning model are better than those who learn with conventional learning in class VII SMP N 15 Padang. This type of research is quasi-experimental and the design used is equivalent posttest-only. The population of this study were class VII students at SMP N 15 Padang. The sampling was done using random sampling with simple random sampling technique, obtained class VII 1 as the experimental group  and VII 2 as the control group. Based on the analysis of mathematical problem-solving ability test data, P-value = 0.00 is obtained with a significant level (α = 0.05), because the P-value < α means that H0 is rejected. The conclusion obtained is that students who study with the Problem Based Learning model are better than those who learn with conventional learning in class VII SMP N 15 Padang. Keywords – Problem Based Learning (PBL), Mathematical Problem Solving Abilities